Postcard from Adolf von Oechelhäuser to Georg Bredig, 1922 - Oechelhäuser, Adolf von (1922)
Postcard to Georg Bredig (1868-1944) from Adolf von Oechelhäuser (1853-1922). The postcard features a black and white portrait of a man, possibly Oechelhäuser. Adolf von Oechelhäuser was an art historian and preservationist. He was a rector at the Technical University of Karlsruhe from 1902-1903 and 1909-1910.
Keywords: Bredig, Georg, 1868-1944; Oechelhäuser, Adolf von, 1852-1923; College teachers; Universität Karlsruhe